2022
DOI: 10.24042/djm.v5i1.11521
|View full text |Cite
|
Sign up to set email alerts
|

The effect of memorizing the Quran on students' mathematical logical intelligence

Abstract: The purpose of this research is to determine the magnitude of the impact of memorizing the Quran on the logical-mathematical intelligence of students at the Private MTs Al-Jamaiyah Medan in the 2021/2022 academic year. This research is research that uses a quantitative approach and a kind of ex-post research. In this research, there are two variables, the independent variable is the memorization of the Quran and the dependent variable is mathematical logical intelligence. The population in this research amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…In addition, the results of this study which showed a significant positive influence, the memorization index of the Quran in Pondok Pesantren Darunnajah 9 is in line with the results of previous studies such as research conducted by (Fatmi et al, 2022), (Asliyah & Ananda, 2022) and (Faiziyah, 2018). This reinforces the initial assumption that reciting the Quran can improve student achievement, especially in Mathematics.…”
Section: Simple Linear Regression Testsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, the results of this study which showed a significant positive influence, the memorization index of the Quran in Pondok Pesantren Darunnajah 9 is in line with the results of previous studies such as research conducted by (Fatmi et al, 2022), (Asliyah & Ananda, 2022) and (Faiziyah, 2018). This reinforces the initial assumption that reciting the Quran can improve student achievement, especially in Mathematics.…”
Section: Simple Linear Regression Testsupporting
confidence: 91%
“…Some previous studies have stated that there is a positive correlation between memorization activities of the Quran with learning achievement and mathematical abilities such as research conducted by (Irsal & Yunita, 2022), (Faiziyah, 2018), (Hikmah et al, 2024), and (Yudha & Rohmadi, 2022). Meanwhile, other studies say that there is a positive and significant influence, memorization of the Qur'an on learning achievement, and mathematical understanding abilities, and / or students' mathematical thinking intelligence, such as research conducted by (Fatmi et al, 2022), (Asliyah & Ananda, 2022), and (Faiziyah, 2018).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation